Partnering to improve gender-responsive monitoring - Morgan, Miranda Yeen; Mora, Catalina (2023)
The CGIAR Initiative on Gender Equality and ISEAL partnered to explore how sustainability systems can contribute to advancing gender equality and women’s empowerment in agri-food systems. As part of this work, a scoping study was conducted with members who identified their main challenges in supporting gender integration. One of the key issues highlighted was the lack of strong data on women and gender equality in value chains and the challenge of how best to monitor and evaluate impacts on gender equality effectively and meaningfully. In response to this need, CGIAR worked with the Sustainable Agriculture Network (SAN) to identify and map gender-responsive monitoring tools and approaches that could be useful to ISEAL Community Members, private sector actors and other interested partners. They shared this as part of the ISEAL Community Member dialogue on sustainability topics series.